(untitled) (Research, Society and Development, 2025)
The use of collagen-based biomaterials in tissue engineering has surged in recent decades due to collagen’s advantages, including biocompatibility, controlled biodegradation, and support for cell adhesion and differentiation. Traditional collagen sources, often from bovine or porcine origins, pose challenges such as zoonotic risks, immunogenic reactions, and ethical concerns. To address these limitations, researchers are exploring innovative collagen sources, such as marine sponges. Collagen from marine sponges, known as spongin (SPG) or spongin-like collagen (SC), exhibits biocompatibility and is considered a natural component for tissue regeneration, serving as a cell-matrix adhesion framework. Our group has conducted experiments over several years to extract SPG from sponges, assess its biocompatibility and cytotoxicity, as well as its in vitro and in vivo biological effects. This research aims to review the data obtained from our research on characterization and in vivo biological performance of collagen-like from marine sponges. Furthermore, combining SPG with ceramics like hydroxyapatite and bioactive glasses has demonstrated beneficial biological properties. Despite ethical and regulatory challenges, marine sponge collagen shows promise as a natural biomaterial that could improve patients’ quality of life, particularly in bone injury treatments. This review highlights the innovative use of marine sponges and their collagen-based components in tissue engineering, emphasizing their potential as a promising alternative for bone injury treatment. Additionally, it underscores the need for further research to fully harness this natural biotechnological resource.